A Chronicle on Medicolegal Cases: The Tertian Care Testimony - C. Yogesh; A. Amirthvarshan; S. Paranthaman; S. Priyanka (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
The study’s goal is to determine the number of medicolegal cases reported in a tertiary care hospital in South India over the course of a year. Profiling of medico-legal cases is an important aspect for the prevention of preventable casualties in future and to study the genuine crime in the area. A retrospective content-based analysis was performed on 776 medicolegal cases recorded in a tertiary care hospital in South India between June 1st, 2017 and May 31st, 2018, and the findings were tabulated. Of the 776 cases, 545 were men and 231 were women, with RTA accounting for 70.74% (549 cases) of the cases and poisoning accounting for 10.69% (83 cases) of the cases, comprising the majority of the case profile. According to the analysis, road traffic accidents are the leading cause of medicolegal cases, followed by poisoning. Preventive measures for improved traffic control and road safety must be implemented as soon as possible. For additional steps, more medicolegal profiling should be undertaken in each region.